Research Commentary—The New Organizing Logic of Digital Innovation: An Agenda for Information Systems Research - Yoo, Youngjin; Henfridsson, Ola; Lyytinen, Kalle (Information Systems Research, 2010)
In this essay, we argue that pervasive digitization gives birth to a new type of product architecture: the layered modular architecture. The layered modular architecture extends the modular architecture of physical products by incorporating four loosely coupled layers of devices, networks, services, and contents created by digital technology. We posit that this new architecture instigates profound changes in the ways that firms organize for innovation in the future. We develop (1) a conceptual framework to describe the emerging organizing logic of digital innovation and (2) an information systems research agenda for digital strategy and the creation and management of corporate information technology infrastructures.